COMPETENCE REQUIREMENTS FOR MANAGEMENT POSITIONS IN AUSTRIAN EMERGENCY ORGANIZATIONS - Rapolter Sascha (2017)
This master thesis deals with the issue of competences and their necessary expression in management and leadership positions. The focus is on the description of the individual education models (from the entry to the trained officer) of the four most important first responders of Austria. These refer to the models of the Austrian Armed Forces, the police, the volunteer fire brigade and the Red Cross. The main focus is on the individual training sections and the mediated competences required for the practice of the officer’s profession. The first two chapters describe the fundamentals and essential definitions concerning the competence topic in order to better understand the scientific findings of this master thesis. The third chapter is devoted to the individual education models of the four operational organizations and shows differences and similarities. The fourth chapter describes the basic structure of the Austrian national and international security strategy in order to show the complex situations and tasks that the Austrian disaster relief forces and leaders have to perform. The empirical analysis is based on four interviews, with one representative of each of the four emergency organizations. The methodological approach and the results are evaluated in chapter six. Chapter seven summarizes the acquired knowledge, answers the research question and gives an outlook on the future.